A genetic variant in CDKN2A/2B locus was associated with poor prognosis in patients with esophageal squamous cell carcinoma. Issue 4 (21st September 2018) - Ghobadi, Niloofar; Mehramiz, Mehrane; ShahidSales, Soodabeh; Rezaei Brojerdi, Arezou; Anvari, Kazem; Khazaei, Majid; Rezayi, Majid; Sadegh Khorrami, Mohammad; Joudi‐Mashhad, Mona; Ramshini, Hassan; Ahmadi‐Simab, Saeideh; Moradi, Ali; et al.
Abstract: Esophageal squamous cell carcinoma (ESCC) is among the leading causes of cancer related death. Despite of extensive efforts in identifying valid cancer prognostic biomarkers, only a very small number of markers have been identified. Several genetic variants in the 9p21 region have been identified that are associated with the risk of multiple cancers. Here, we explored the association of two genetic variants in the 9p21 region, CDKN2A/B, rs10811661, and rs1333049 for the first time in 273 subjects with, or without ESCC. We observed that the patients with ESCC had a higher frequency of a TT genotype for rs10811661 than individuals in the control group, and this polymorphism was also associated with tumor size. Moreover, a CC genotype for the rs1333049 polymorphism was associated with a reduced overall survival (OS) of patients with ESCC. In particular, patients with a CC (rs1333049) genotype had a significantly shorter OS (CC genotype: 34.5 ± 8.9 months vs. CG+GG: 47.7 ± 5.9 months; p value = 0.03). We have also shown the association of a novel genetic variant in CDKN2B gene with clinical outcome of patients with ESCC. Further investigations are warranted in a larger population to explore the value of emerging markers as a risk stratification marker in ESCC. Abstract : Kaplan‐Meier survival curves. a) Overall Survival (OS) and b) Progression‐Free Survival (PFS) based on different genotypes of CDKN2B rs1333049 polymorphism. p values were calculated with the logrank test